Improving the sensitivity of myelin oligodendrocyte glycoprotein-antibody testing: exclusive or predominant MOG-IgG3 seropositivity : a potential diagnostic pitfall in patients with MOG-EM/MOGAD - Jarius, Sven; Ringelstein, M.; Schanda, K.; Ruprecht, K.; Korporal-Kuhnke, Mirjam; Viehöver, Andrea Maria; Hümmert, M. W.; Schindler, P.; Endmayr, V.; Gastaldi, M.; Trebst, C.; Franciotta, D.; et al. (Journal of neurology, 2024)
Myelin oligodendrocyte glycoprotein antibody-associated encephalomyelitis (MOG-EM; also termed MOG antibody-associated disease, MOGAD) is the most important differential diagnosis of both multiple sclerosis and neuromyelitis optica spectrum disorders. A recent proposal for new diagnostic criteria for MOG-EM/MOGAD explicitly recommends the use of immunoglobulin G subclass 1 (IgG1)- or IgG crystallizable fragment (Fc) region-specific assays and allows the use of heavy-and-light-chain-(H+L) specific assays for detecting MOG-IgG. By contrast, the utility of MOG-IgG3-specific testing has not been systematically evaluated.